Assessing the financial condition and accounts receivable risk among US farmer cooperatives. Issue 2 (18th October 2021) - Mashange, Gerald; Briggeman, Brian C.
Abstract : Purpose: The purpose of this paper is to examine the financial condition and ability of farmer cooperatives to withstand significant increases in bad debt expense. Design/methodology/approach: A unique data set of farmer cooperative financial statements that spans from 1996 to 2019 is used to examine the changes in profitability, solvency, liquidity and accounts receivable risk. Also, a deterministic stress test model is designed to shock bad debt expense and the resulting write-off of accounts receivable for farmer cooperatives. The stress test provides insights to the resiliency of farmer cooperatives. Findings: Results find that farmer cooperatives are in a strong financial position, which has improved over time. The majority of farmer cooperatives are able to absorb a substantial increase in bad debt expense because of their sizable, retained earnings position. However, cooperatives that have significant profitability challenges do experience much larger losses, especially mixed farmer cooperatives (roughly equally amounts of grain and farm supply sales) and large cooperatives with more than $500 million in sales. Practical implications: The stress test results suggest farmer cooperative managers and boards of directors could re-examine their credit policies and consider extending additional credit. Also, cooperatives should consider monitoring and identifying an optimal accounts receivable to retained earnings ratio, which is similar to how banks examine their tier 1 capital ratios. Originality/value: The value of this study is having data that allows for the examination of the financial condition of farmer cooperatives over time. Also, having current data means the accounts receivable stress test results are more relevant and timelier. This is important because these accounts receivable are primarily tied to crop input supplies, and farmer cooperatives are a significant market participant in the crop input supply market.